Legal Protection of Personal Data in the Exchange of Electronic Medical Record in Healthcare Services - Takaryanto, Davin; Lany, Arman (LifeSciFi, 2025)
Digital transformation in Indonesia’s health sector has fundamentally changed the way patient information is collected, stored, and managed through Electronic Medical Records (EMR). This study aims to (1) map the active legal basis governing the confidentiality of EMRs in Indonesia; (2) identify normative and practical gaps in its implementation; (3) propose auditable technical and governance standards for healthcare facilities and system providers; and (4) outline procedural and judicial mechanisms for resolving health data breach disputes. Using a normative legal approach, this study analyzes the constitutional, legislative, and regulatory legal framework, such as Law Number 17 of 2023 concerning Health, Law Number 27 of 2022 concerning Personal Data Protection, Law Number 1 of 2024 concerning Electronic Information and Transactions, Government Regulation Number 71 of 2019, and Minister of Health Regulation Number 24 of 2022. The results of the study show overlapping authorities, weak institutional coordination, and the absence of procedural standards related to the verification of RME in court. The study’s findings reveal that EMR confidentiality protection in Indonesia is weak not due to a lack of legal regulations, but due to inadequate technical readiness and governance for its implementation.